2006
DOI: 10.1257/089533006776526111
|View full text |Cite
|
Sign up to set email alerts
|

Some Uses of Happiness Data in Economics

Abstract: Economists are trained to infer preferences from observed choices; that is, economists typically watch what people do, rather than listening to what people say. Happiness research departs from this tradition. Instead, happiness researchers have been particularly interested in self-reports of well-being, which may be as simple as an answer to a question with the general form: "Are you very happy, pretty happy, or not too happy?" Hundreds of thousands of individuals have been asked this kind of question, in many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
323
1
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 687 publications
(361 citation statements)
references
References 51 publications
13
323
1
7
Order By: Relevance
“…In our study, we find that the level of income relative to others in the economy is not a key driver of satisfaction, but changes in income over time affects the satisfaction with income, and also overall satisfaction with fishing. This is in contrast to studies or other industries or groups (e.g., Tella and MacCulloch 2006;Clark et al 2008) which suggest that change in incomes is less important than relative income. In most occupations, incomes tend to move in a positive direction (at least in nominal terms).…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…In our study, we find that the level of income relative to others in the economy is not a key driver of satisfaction, but changes in income over time affects the satisfaction with income, and also overall satisfaction with fishing. This is in contrast to studies or other industries or groups (e.g., Tella and MacCulloch 2006;Clark et al 2008) which suggest that change in incomes is less important than relative income. In most occupations, incomes tend to move in a positive direction (at least in nominal terms).…”
Section: Discussioncontrasting
confidence: 88%
“…While income adds to life satisfaction up to a certain point, beyond that point additional income does very little (Cummins 2000). Others have found that individual satisfaction is generally found to be correlated with relative income (Tella and MacCulloch 2006;Clark et al 2008;Boyce et al 2010), meaning the level of income relative to others or how that income has changed relative to others. However, overall happiness or satisfaction is affected by a wide range of factors other than income, including an individual's personal circumstances (including their health, relationships, and ability to achieve desired outcomes from life, factors often correlated with demographic characteristics such as marital status, age, education and household characteristics), and the broader societal circumstances they live in (such as whether they live in a safe community, have positive social capital, and a just and fair government, to name a few) (Peiró 2006;Vemuri and Costanza 2006;Welsch 2009;Frey and Stutzer 2010;Diener et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SWB metrics have been shown to be psychometrically sound, internally consistent and comparable across individuals, over time, and for different levels of economic development (Diener et al, 1999;Helliwell et al, 2010;Krueger & Schkade, 2008). Further, they are increasingly used in public policy and economic analyses (Diener et al, 2009;Di Tella & MacCulloch, 2006;O'Donnell, 2013;Stiglitz et al, 2010;Stone & Mackie, 2013). Indeed, some countries (e.g., Bhutan, Britain, and France) are now including SWB metrics in official statistics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…", again with a VAS between 1 = Very unhappy and 10 = Very happy (Table 1). These questions draw upon a longstanding literature in psychology (Diener, Suh, Lucas, & Smith, 1999) and their use is rapidly expanding and gaining prominence within economics more generally (Di Tella & MacCulloch, 2006) and health economics in particular (Oswald & Powdthavee, 2008). Subjective well-being questions have been validated and modelled across contexts and countries (Blanchflower & Oswald, 2004) and are regarded as good empirical approximation of individual well-being and utility (Frey & Stutzer, 2002;Oswald & Powdthavee, 2008).…”
Section: Outcomes Of Interestmentioning
confidence: 99%